An Investigation on the Regenerative Effects of Intra Articular Injection of Co-Cultured Adipose Derived Stem Cells with Chondron for Treatment of Induced Osteoarthritis - Sorayya Jacer; Hajar Shafaei; Jafar Soleimani Rad (Tabriz University of Medical Sciences, 2018)
Purpose: Adipose tissue derived stem cells (ASCs) and chondrocytes are best cells for articular cartilage regeneration. Chondrocyte with peri-cellular matrix (PCM) is called chondron provides ideal microenviroment than chondrocytes. We aimed to evaluate the regenerative effects of intra-articular injection of ASCs co-cultures with chondron in induced osteoarthritis (OA). Methods: ASC, from the peri-renal fat of male rat and chondron from primary newborn rat hyaline cartilage were isolated. ASCs were cultured for at least three passages in vitro. Six weeks after OA induction, rats were randomly distributed in five groups of control, osteoarthritic, ASC, chondron and co-cultured. ASCs (107), chondrons (107) and combination of chondrons and ASCs (107) were injected into intra-articular space of the rat knee. The effect of treatments was evaluated by macroscopic and microscopic examinations. The expression levels of collagen type ΙΙ was studied by immunohistochemistry. Results: Macroscopic appearance of the co-cultured group, showed much enhanced articular cartilage regeneration compared to ASC and chondron groups. H&E showed evidence of repair site of articular surface without erosion and fibrillation versus OA group which showed thin layer of hyaline cartilage over tidemark and spontaneous fibrocartilage formation. Metachromatic regions stained with toluidine blue were larger in treatment groups versus OA group. Strong intensity of type ΙΙ collagen staining was observed in co-culture group compared to other groups. Conclusion: Co-culture of chondrons and ASCs increased articular hyaline cartilage formation and provides a useful tool to improve limitations of each of applied cells in this model.